2018
DOI: 10.1007/s00784-018-2625-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival percentages of atraumatic restorative treatment (ART) restorations and sealants in posterior teeth: an updated systematic review and meta-analysis

Abstract: ART is an effective evidence-based option for treating and preventing carious lesions in primary and permanent posterior teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
2
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 108 publications
3
102
2
13
Order By: Relevance
“…HVGIC showed, in our study, the worst retention rate (0.671), similar to other studies that found a 65% survival rate in multi-surface ART restorations using HVGIC 74 or failures in 30% of class II ART restorations during the first month using HVGIC 52 . A study that compared the use of HVGIC using ART versus a conventional cavity Table 3.…”
Section: Discussionsupporting
confidence: 91%
“…HVGIC showed, in our study, the worst retention rate (0.671), similar to other studies that found a 65% survival rate in multi-surface ART restorations using HVGIC 74 or failures in 30% of class II ART restorations during the first month using HVGIC 52 . A study that compared the use of HVGIC using ART versus a conventional cavity Table 3.…”
Section: Discussionsupporting
confidence: 91%
“…The provision of care under the threat of COVID-19 or other air-borne infections, will require the adoption of new techniques for infection control in dental settings. Additional emphasis on the reduction of aerosols may result in increased usage of non-aerosol generating treatments for carious lesions, such as silver diamine fluoride, temporary restorations with glass ionomers, or atraumatic restorative treatments (30)(31)(32). Providers should be prepared for evolving guidance and continued adjustments to the way they practice, as evidence-based research is established for COVID-19 and dental treatment.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, another systematic review found that composite resin, compomer, resin-modified glass ionomer cement, and glass ionomer cement showed similar results for the restoration of primary molars [52]. Although ART could be considered an alternative for restoring occlusal [53] and occlusoproximal [53,54] cavities in primary molars, just six guidelines cited it. Bearing all these aspects in mind, the clinical decision-making to choose one material should consider besides the type of cavity, the patient's/family's wish, the professional's ability, the child's age, the child's behavior and treatment' costs and availability.…”
Section: Discussionmentioning
confidence: 99%